How asymmetric mating patterns affect the rate of neutral genetic substitution - Belanger, Emma; Seard, Aisha; Hoang, Aysha; Tran, Amanda; Antonio, Lorhena Guimaraes; Dementieva, Yulia A.; Sample, Christine; Allen, Benjamin (Frontiers in Ecology and Evolution, 2023)
A population under neutral drift is expected to accumulate genetic substitutions at a fixed "molecular clock" rate over time. If the population is well-mixed, a classic result equates the rate of substitution per generation to the probability of mutation per birth. However, this substitution rate can be altered if individual birth and death rates vary by class or by spatial location. Here we investigate how mating patterns affect the rate of neutral genetic substitution in a diploid, sexually reproducing population. Using a general mathematical modeling framework, we demonstrate that if survival rates and mating opportunities vary systematically across individuals, the rate of neutral substitution can be either accelerated or slowed. In particular, this can occur in populations with uneven sex ratio at birth, or with reproductive skew.